Opportunistic salpingectomy versus tubal ligation. A review of current strategies for ovarian cancer prevention - Miciak, Aleksandra Anna; Węglarz, Aleksandra Karolina; Borowiecka, Patrycja Anna; Adamarczuk, Jagoda Anna; Głuski, Jacek; Urantówka, Nina; Wojtera, Aleksandra; Omiecińska, Marta; Kaszowska, Karina Barbara; Dąbrowski, Tomasz Piotr; Kaczmarz-Chojnacka, Karolina (Journal of Education, Health and Sport, 2026)
Introduction and purpose. Ovarian cancer is a leading cause of gynecological mortality due to late diagnosis. Modern evidence shows that high-grade serous ovarian cancer (HGSC) often originates in the fallopian tube from serous tubal intraepithelial carcinoma (STIC) lesions. This supports opportunistic salpingectomy as a superior preventive strategy over traditional tubal ligation. This study compares both methods regarding oncological efficacy, surgical safety, and impact on ovarian reserve. Material and method. In January 2026, a comprehensive narrative review was conducted using PubMed, Google Scholar, and JEHS archives. The analysis focused on 20 key publications (2017–2025) comparing salpingectomy and tubal ligation, focusing on HGSC prevention, Anti-Müllerian hormone (AMH) levels, and cost-effectiveness. Results. Population data indicate that salpingectomy is more effective, reducing HGSC risk by 65–80%, compared to 24–28% for tubal ligation. Surgical analysis shows salpingectomy extends operative time by 8–15 minutes but does not increase perioperative risk. Systematic reviews show no significant decrease in AMH levels post-surgery, though a potential risk of exacerbating genitourinary syndrome was noted. Economic analyses confirm that opportunistic salpingectomy is highly cost-effective by avoiding advanced cancer treatment expenses. Conclusions. Opportunistic salpingectomy is the gold standard for prevention in women completing their reproductive plans. It is safe, preserves hormonal function, and offers superior protection compared to tubal ligation. Preoperative counseling regarding quality of life is recommended.